1998
DOI: 10.1074/jbc.273.48.32009
|View full text |Cite
|
Sign up to set email alerts
|

S-Nitroglutathione, a Product of the Reaction between Peroxynitrite and Glutathione That Generates Nitric Oxide

Abstract: Peroxynitrite (ONOO؊ ) has been shown in studies on vascular relaxation and guanylate cyclase activation to react with glutathione (GSH), generating an intermediate product that promotes a time-dependent production of nitric oxide (NO). In this study, reactions of ONOO ؊ with GSH produced a new substance, which was characterized by liquid chromatography, ultraviolet spectroscopy, and electrospray tandem mass spectrometry. The mass spectrometric data provided evidence that the product of this reaction was S-nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
2
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(74 citation statements)
references
References 23 publications
(32 reference statements)
1
68
2
1
Order By: Relevance
“…Although S-nitroso-N-acetylpenicillamine, an agent that S-nitrosates cysteine residues (46), had no effect on PGHS-1 activity (15,17), it was recently reported that S-nitrosation enhances the activation of PGHS-2 (18). ONOO 2 has been reported to generate S-nitroglutathione from GSH (47) and is involved in the formation of sulfenic (-SO), sulfinic (-SO 2 ), and sulfonic (-SO 3 ) moieties (44). Thus, the involvement of cysteine oxidation in PGHS-1 function cannot be discounted and will be the focus of separate studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although S-nitroso-N-acetylpenicillamine, an agent that S-nitrosates cysteine residues (46), had no effect on PGHS-1 activity (15,17), it was recently reported that S-nitrosation enhances the activation of PGHS-2 (18). ONOO 2 has been reported to generate S-nitroglutathione from GSH (47) and is involved in the formation of sulfenic (-SO), sulfinic (-SO 2 ), and sulfonic (-SO 3 ) moieties (44). Thus, the involvement of cysteine oxidation in PGHS-1 function cannot be discounted and will be the focus of separate studies.…”
Section: Discussionmentioning
confidence: 99%
“…A proposed mechanism for this NO generation is a homolysis-recombination pathway of thionitrate: RSNO 2 3 (RS ⅐ , ⅐ NO 2 ) 3 RSONO 3 RSO ⅐ ϩ ⅐ NO. Indeed, NO release from GSNO 2 was demonstrated by Balazy et al (37), suggesting indirectly that GSH sulfinyl radical (GSO ⅐ ), which is the counterpart of sulfenyl nitrite and sulfinyl nitrite for NO, may be generated to yield disulfide S-oxide in the proteins.…”
Section: Characterization Of S-glutathiolation Of Prommps By Maldi-tomentioning
confidence: 99%
“…GSNO 2 was prepared and purified according to the method of Balazy et al (37). Briefly, GSH was nitrated by reaction with NO 2 BF 4 (Aldrich) at a molar ratio 1:4 (GSH:NO 2 BF 4 ) in 10 mM phosphate-buffered saline (pH 7.4) for 10 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The product of O 2 . ϩ NO, ONOO Ϫ , mostly rearranges to form biologically inert nitrite or reacts with GSH to form the NO donor GSNO (19,23,24). However, when the [NO] approaches that of SOD, the resulting high levels of ONOO Ϫ produce a number of cell-damaging effects (19,24).…”
mentioning
confidence: 99%